The Concept of Citizenship in the Polish School Education. Political Change and the Change of Core Curricula. Discourse Analysis - Violetta Kopińska (Nicolaus Copernicus University in Toruń, 2020)
The present article examines the problem of applying the concept of citizenship inherent in the discourse of a political party to core curricula (CCs). The case that provides material for analysis is the coming to power of the conservative party Prawo i Sprawiedliwość [Law & Justice] (PIS) and the implemented reform of the education system, which entailed the change of CCs. The analytical tool useful for solving the analysed problem is provided by the concept of 'discursive institutionalism' of Vivien Schmidt, integrated with the concept of curriculum analysis, while the method of analysis comes from the group of approaches defined as Critical Discourse Analysis (CDA). The analyses focus on the programmatic level and reveal the application of ideas from the party's programmes to the education objectives articulated in CCs. The findings of the analyses indicate a stronger-than-before emphasis on the idea of a political and national community. Particularly interesting in the analysed case is the focus on the transmission of knowledge, the upbringing according to the values affirming this feeling of community, combined with the simultaneous discursive limitation of the significance of civic participation.